Reinterpreting potential biomarker in umbilical cord as a marker of chorioamnionitis and funisitis in prelabor ROM - Julian Dewantiningrum; Besari Adi Pramono; Agoes Oerip Poerwoko; Budi Irawan; Rizky Aditya Bachrudin; Herman Kristanto (Universitas Airlangga, 2025)
HIGHLIGHTS HsCRP and IL-6 levels in umbilical cord blood serve as reliable early biomarkers of chorioamnionitis and funisitis in prelabor ROM, enabling more accurate neonatal sepsis risk assessment and targeted clinical intervention. Early identification of amnionitis and funisitis through hsCRP and IL-6 measurements guides timely clinical decisions, including prompt antibiotics or intensified monitoring, thereby reducing severe neonatal complications. ABSTRACT Objective: Prelabor rupture of membranes (ROM) occurs in approximately 1% of all pregnancies and 30% of all preterm births, and the etiology remains unclear. Prelabor ROM is associated with a high incidence of funisitis and chorio-amnionitis leading to neonatal sepsis. This study aimed to assess whether hsCRP, procalcitonin, and IL-6 level in umbilical cord as indicators for identifying pregnancies at risk for these complications. Materials and Methods: This research used cross sectional design conducted in dr. Kariadi Hospital. Inclusion criteria were pregnant woman with 28-42 weeks of gestational age, singleton and prelabor ROM. Exclusion criteria included other comorbidities. The participants were divided into two groups: with and without funisitis-chorioamnionitis, which were detected using histopathologic examination. Statistical analysis was performed using the chi-square, t-test/Mann-Whitney between two group, wit statistically significant set at p<0.05. Results: A total of 88 pregnant women were included in the study, consisting of 23 pregnant women with chorioamnionitis-funisitis and 65 pregnant women without funisitis-chorioamnionitis. Procalcitonin levels in the group with and without chorioamnionitis-funisitis were 0.88±0.6 vs 1.06±0.46 ug/mL (p=0.07). IL-6 levels in the chorioamnionitis-funisitis were 54.41(9.34-445.9) vs 2.83(0.09-454.82) pg/mL in without chorioamnionitis-funisitis (p<0.001). HsCRP levels in the funisitis-chorioamnionitis compared to those without chorioamnionitis-funisitis group were 1.39(0.07-10.5) vs 0.17(0.03-10.5) mg/L (p<0.001). Conclusion: Elevated levels of hsCRP and IL-6 in the umbilical cord were found to be significant biomarkers for chorioamnionitis and funisitis in prelabor rupture of membranes. These biomarkers could be useful in identifying pregnant women at high risk for these complications, enabling better clinical management.